Characterization of proteins with Siaα2-3/6Gal-linked glycans from bovine milk and role of their glycans against influenza A virus. Issue 10 (4th September 2018) - Yu, Hanjie; Zhong, Yaogang; Zhang, Zhiwei; Liu, Xiawei; Zhang, Kun; Zhang, Fan; Zhang, Jing; Shu, Jian; Ding, Li; Chen, Wentian; Du, Haoqi; Zhang, Chen; et al.
Abstract : The bovine milk proteins have a wide range of functions, but the role of the attached glycans in their biological functions has not been fully understood yet. Abstract : The bovine milk proteins have a wide range of functions, but the role of the attached glycans in their biological functions has not been fully understood yet. Here, the glycopatterns of whole bovine milk proteins were analyzed using lectin microarrays. Then, the proteins with Siaα2-3/6Gal-linked glycans were isolated and characterized. The roles of Siaα2-3/6Gal-linked glycans of the isolated proteins were assessed by inhibiting viral activity against influenza A viruses (IAV). In total, there were 69 sialylated proteins to be identified and annotated. The sialylated proteins have the ability to inhibit the attachment of IAV mimics to MDCK cells; however, the role of inhibition was abolished when the sialic acid moieties were destroyed. The results demonstrate that the sialic acid moieties of proteins could serve as competitive substrates to disturb the viral attachment to cell surface receptors. Our findings will help to assess the potential application of sialylated glycoproteins in bovine milk against IAV.